Positive electrode tab glue, positive electrode tab glue slurry, positive electrode plate and secondary battery

By using an acrylate polymer system to coat the ceramic/polymer composite coating on the surface of the positive electrode aluminum foil, the problems of low wet viscosity strength and limitations of the existing positive electrode ear glue materials are solved, and higher adhesion and battery performance are achieved.

CN119912884AActive Publication Date: 2025-05-02SHENZHEN HAODYNE TECH CO LTD

Patent Information

Application Number
CN202510404893.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-02
Publication Date
2025-05-02
Estimated Expiration
2045-04-02

AI Technical Summary

Technical Problem

The existing positive electrode ear glue materials have low wet viscosity strength, limitations of aluminum foil curling and safety hazards, which affect the processing performance and safety of lithium-ion secondary batteries.

Method used

The acrylate polymer system is used to replace the traditional PVDF system, and the ceramic/polymer composite coating is coated on the surface of the positive electrode aluminum foil substrate through a thermal composite process to improve the adhesion with the separator.

Benefits of technology

It improves wet viscosity strength and aluminum foil curling, improves the adhesion between the composite ceramic aluminum foil and the separator, thereby improving the processing performance and safety of the battery and improving the cell circulation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912884A_ABST
    Figure CN119912884A_ABST
Patent Text Reader

Abstract

The positive electrode tab glue provided by the invention comprises an acrylate polymer, an organic salt and an organic solvent, the molecular weight Mw of the acrylate polymer is 10-35w, and the organic salt accounts for 0.1-0.8% of the weight of the acrylate polymer; the acrylate polymer comprises hard-segment resin and soft-segment resin, the glass-transition temperature Tg of the hard-segment resin is greater than or equal to 20 DEG C, and the glass-transition temperature Tg of the soft-segment resin is less than or equal to 0 DEG C. The preparation method comprises the following steps: mixing positive electrode tab glue and ceramic particles in proportion to obtain positive electrode tab glue slurry, coating the positive electrode tab glue slurry and the positive electrode slurry at the same time, coating an aluminum foil on the edge of a positive electrode plate, and drying to obtain the positive electrode plate with a functional coating. When the positive pole piece is applied to the lithium ion secondary battery, the bonding strength between the positive pole piece and an aluminum foil and a diaphragm can be improved, the processability, safety and other performances of the battery are improved, and the cycle performance of a battery cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a positive electrode tab glue, a positive electrode tab glue slurry, a positive electrode plate and a secondary battery. Background Art

[0002] Lithium-ion secondary batteries are usually mainly composed of a positive electrode, a negative electrode, a separator, an electrolyte, and a battery casing. The separator is one of the key internal components, and its main function is to separate the positive and negative electrodes of the battery to prevent the positive and negative electrodes from contacting and short-circuiting.

[0003] There are many processing problems in the processing of lithium-ion secondary batteries, which will affect the battery performance. Since the positive electrode is generally smaller than the negative electrode, burrs are easily generated on the edge of the wide side of the electrode during cutting. Once the diaphragm is pierced and the negative electrode is contacted, it will cause a short circuit in the battery. Since the surface of boehmite is smooth, after using boehmite to coat the edge of the positive electrode, the edge of the positive electrode can be filled, making the surface smooth and burr-free after cutting.

[0004] There are many factors that affect the safety of lithium-ion secondary batteries. Among them, the cracking of the tabs of the composite diaphragm easily causes burrs, abnormal protrusions and fractures in the subsequent electrode assembly process, which causes battery safety issues that have attracted much attention in recent years. Since the tabs are the key components for the on-current connection of lithium-ion batteries, the tabs are usually cut from the edges of the pole pieces. In the battery core structure, part of the root of the positive tab overlaps with the negative active material area.

[0005] During the preparation of the battery cell, the problem of misalignment of the tabs may occur. The tabs can be bonded to the diaphragm to improve the misalignment. To improve the safety of lithium-ion batteries, a ceramic layer is applied to the overlapping area of ​​the tabs of the positive electrode.

[0006] In order to solve the above problems, a positive electrode tab glue is urgently needed. Ceramic particles are coated on the surface of the positive electrode aluminum foil substrate to form a ceramic / polymer composite coating, and a thermal composite process is used to achieve bonding between the positive electrode aluminum foil and the diaphragm, thereby improving short circuits and tab dislocation caused by edge burrs.

[0007] The positive electrode ear glue has a high peel strength requirement. After coating, it is bonded to the positive electrode aluminum foil substrate, and after thermal compounding, it is bonded to the PP / PE / ceramic separator. At the same time, because the positive electrode ear glue slurry and the positive electrode slurry are coated at the same time, it is required that there is no cross-linking between the positive electrode ear glue slurry and the positive electrode slurry, and there are specific requirements for the physical properties of the positive electrode ear glue slurry.

[0008] The positive electrode ear glue currently used in the market is mainly based on the PVDF (polyvinylidene fluoride) system. However, the most obvious disadvantage of PVDF is its poor peel strength and poor wet adhesion. It will peel off after being immersed in electrolyte for a long time, which poses certain safety hazards. It will also cause obvious deformation of the battery cell in the later stage of the cycle, resulting in a decrease in capacity.

[0009] The adhesion between the diaphragm and the safety coating interface of the pole piece has a great impact on safety. There is an urgent need for a material that can improve the adhesion between the composite ceramic aluminum foil and the diaphragm, thereby improving the processing performance and safety of the battery and improving the cycle performance of the battery cell. Summary of the invention

[0010] In order to solve the problems existing in the existing positive electrode tab glue materials, the purpose of the present invention is to provide a positive electrode tab glue, a positive electrode tab glue slurry, a positive electrode plate and a secondary battery.

[0011] The present invention achieves the technical effects through the following technical solutions: In the first aspect, the positive electrode ear glue provided by the present invention includes an acrylic polymer, an organic salt and an organic solvent, the molecular weight Mw of the acrylic polymer is 10w~35w, and the weight percentage of the organic salt in the acrylic polymer is 0.1%~0.8%; the acrylic polymer includes a hard segment resin and a soft segment resin, the glass transition temperature Tg of the hard segment resin is ≥ 20°C, and the glass transition temperature Tg of the soft segment resin is ≤ 0°C.

[0012] Preferably, the weight percentage of the organic salt to the acrylic ester polymer is 0.4% to 0.8%.

[0013] Preferably, the glass transition temperature Tg of the hard segment resin is 20 to 90°C, and the glass transition temperature Tg of the soft segment resin is -60 to 0°C.

[0014] Preferably, the mass ratio of the hard segment resin to the soft segment resin is (20-35):(65-80).

[0015] Preferably, the hard segment resin includes a first main structural unit and a first polar structural unit; the soft segment resin includes a second main structural unit and a second polar structural unit; the first main structural unit and the second main structural unit both include acrylate structural units, and each independently and selectively contains an aromatic vinyl structural unit, and the first polar structural unit and the second polar structural unit are independently selected from structural units containing polar groups; the polar groups include one or more of carboxyl, cyano, hydroxyl, epoxy, amino, amide, and acetoxy.

[0016] Preferably, the mass ratio of the first main structural unit to the first polar structural unit is (80-97):(3-20); the mass ratio of the second main structural unit to the second polar structural unit is (75-97):(3-25).

[0017] Preferably, the content of structural units containing carboxyl groups in the acrylic ester polymer is 2-15 wt %.

[0018] Preferably, the acrylic acid ester structural unit is selected from one or more of methyl methacrylate structural unit, methyl acrylate structural unit, ethyl acrylate structural unit, butyl acrylate structural unit, sine octyl acrylate structural unit, isooctyl acrylate structural unit, hexyl acrylate structural unit, cyclohexyl methacrylate structural unit, isobornyl acrylate structural unit, and isobornyl methacrylate structural unit. The aromatic vinyl structural unit is selected from one or a combination of styrene structural unit and methyl styrene structural unit.

[0019] Preferably, the first polar structural unit and the second polar structural unit can be independently selected from one or a combination of two of a methacrylic acid structural unit, an acrylic acid structural unit, an acrylonitrile structural unit, a hydroxyethyl acrylate structural unit, a hydroxyethyl methacrylate structural unit, a hydroxypropyl methacrylate structural unit, a glycidyl methacrylate structural unit, an allyl glycidyl ether structural unit, a dimethylaminoethyl acrylate structural unit, a dimethylaminoethyl methacrylate structural unit, a tert-butylaminoethyl methacrylate structural unit, an acrylamide structural unit, a diacetone acrylamide structural unit, a hydroxymethyl acrylamide structural unit, an acetoacetoxyethyl methacrylate structural unit, a butyl itaconate structural unit, and a β-acryloxypropionic acid structural unit.

[0020] Preferably, the carboxyl-containing structural unit in the acrylic ester polymer is selected from methacrylic acid structural unit and acrylic acid structural unit, or a combination of both.

[0021] The acrylic ester structural units, aromatic vinyl structural units, polar structural units, etc. selected from the hard segment resin and the soft segment resin may be the same or different and must meet the corresponding glass transition temperature Tg requirements.

[0022] Preferably, the hard segment resin further comprises a first post-reaction structural unit containing a post-reaction group, and the soft segment resin further comprises a second post-reaction structural unit containing a post-reaction group, and the first post-reaction structural unit and the second post-reaction structural unit are connected to each other through a chemical bond. It is understandable that the above structure can be obtained by reacting a first post-reaction monomer containing a post-reaction group with a second post-reaction monomer containing a post-reaction group.

[0023] Preferably, the first post-reaction structural unit accounts for 3-10% by weight of the hard segment resin, and the second post-reaction structural unit accounts for 3-10% by weight of the soft segment resin.

[0024] Preferably, the post-reaction group is selected from one or more of carboxyl, amino, epoxy, and acetoxy groups; it is understandable that the post-reaction group on the first post-reaction monomer must be able to react with the post-reaction group on the second post-reaction monomer. For example, the post-reaction group in the first post-reaction monomer is a carboxyl group and / or an amino group, and the corresponding post-reaction groups in the second post-reaction monomer are epoxy and / or acetoxy groups. That is, when the post-reaction group in the first post-reaction monomer is a carboxyl group, the post-reaction group in the second post-reaction monomer is an epoxy group; when the post-reaction group in the first post-reaction monomer is an amino group, the post-reaction group in the second post-reaction monomer is an epoxy group and / or an acetoxy group.

[0025] Preferably, the first post-reaction monomer is selected from one or more of β-acryloxypropionic acid, methacrylic acid, acrylic acid, dimethylaminoethyl acrylate, dimethylaminoethyl methacrylate, tert-butylaminoethyl methacrylate, glycidyl methacrylate, allyl glycidyl ether, and acetoacetoxyethyl methacrylate; the second post-reaction monomer is selected from one or more of β-acryloxypropionic acid, methacrylic acid, acrylic acid, dimethylaminoethyl acrylate, dimethylaminoethyl methacrylate, tert-butylaminoethyl methacrylate, glycidyl methacrylate, allyl glycidyl ether, and acetoacetoxyethyl methacrylate.

[0026] In the hard segment resin, the monomers forming the first polar structural unit include the first post-reaction monomer and the monomers of other polar structural units; the monomers forming the first polar structural unit may be the same as the first post-reaction monomer. When the monomers forming the first polar structural unit are the same as the first post-reaction monomer, the amount of the monomers of the first polar structural unit only needs to satisfy the range of the mass ratio of the first main structural unit to the first polar structural unit, and the structural unit of the first post-reaction group accounts for 3-10% of the weight of the hard segment resin.

[0027] Similarly, in the soft segment resin, the monomers forming the second polar structural unit include the second post-reaction monomer and the monomers of other polar structural units; the monomers forming the second polar structural unit can be the same as the second post-reaction monomer. When the monomers forming the second polar structural unit are the same as the second post-reaction monomer, the amount of the monomers of the second polar structural unit only needs to satisfy the range of the mass ratio of the second main structural unit to the second polar structural unit, and the structural unit of the second post-reaction group accounts for 3-10% of the weight of the soft segment resin.

[0028] Preferably, the molar ratio of the post-reaction group on the first post-reaction monomer to the post-reaction group on the second post-reaction monomer is (0.9-1.1): 1. In the present invention, when the molar ratio of the two is not within the above preferred range, the presence of the excess post-reaction group does not significantly affect the performance of the positive electrode ear glue.

[0029] When the monomer forming the first polar structural unit, the monomer forming the second polar structural unit and the first post-reaction monomer all contain carboxyl groups, the mass ratio of the total amount of carboxyl-containing monomers in the monomer forming the first polar structural unit and the monomer forming the second polar structural unit to the total amount of monomers for preparing the acrylic polymer is taken as the content of the structural unit containing carboxyl groups in the acrylic polymer.

[0030] Preferably, the solid content of the positive electrode ear glue is 18-22%, the organic salt includes at least one of alkyl sulfonate, alkyl sulfate, and alkylbenzene sulfonate, and the organic solvent includes NMP (N-methylpyrrolidone).

[0031] Preferably, the positive electrode ear glue is used for a ternary positive electrode, and when it is coated simultaneously with the ternary positive electrode slurry, the molecular weight Mw of the acrylic polymer is 10w~35w; or, the positive electrode ear glue is used for a lithium iron phosphate positive electrode, and the molecular weight Mw of the acrylic polymer is 20w~35w.

[0032] In a second aspect, the present invention provides a positive electrode ear glue slurry, comprising ceramic particles and the aforementioned positive electrode ear glue, wherein the mass ratio of the ceramic particles to the positive electrode ear glue is (80~95):(5~20). The positive electrode ear glue and the ceramic particles are mixed in proportion to obtain the positive electrode ear glue slurry. Preferably, the mass ratio of the ceramic particles to the positive electrode ear glue is (80~85):(15~20).

[0033] In a third aspect, the present invention provides a positive electrode sheet, including a functional coating obtained by drying the positive electrode tab slurry. The positive electrode tab slurry and the positive electrode slurry are simultaneously coated on the aluminum foil at the edge of the positive electrode sheet, and dried to obtain a positive electrode sheet with a functional coating.

[0034] In a fourth aspect, the present invention provides a secondary battery comprising a negative electrode sheet, a separator, an electrolyte and the aforementioned positive electrode sheet.

[0035] Compared with the prior art, the present invention has the following beneficial effects: The present application adopts an acrylic polymer system to replace the traditional PVDF system as the positive electrode ear glue, which solves the limitations of low wet adhesion strength and aluminum foil curling of existing products. The positive electrode ear glue of the acrylic polymer of the present application can not only improve the wet adhesion strength, but also effectively improve the aluminum foil curling due to the good flexibility of the acrylic polymer; and, due to its high wet adhesion strength, it can improve the battery cycle performance. The positive electrode ear glue is mixed with ceramic particles to form a ceramic / polymer composite coating slurry, which is applied to the aluminum foil at the edge of the pole piece together with the positive electrode slurry, and the bonding between the pole piece and the diaphragm is achieved through hot pressing with the PP / PE / ceramic diaphragm, which can improve the bonding between the composite ceramic aluminum foil and the diaphragm, thereby improving the processing performance and safety of the battery, and improving the battery cell cycle performance.

[0036] The acrylic polymer of the present application has a soft segment resin and a hard segment resin. When used, the two resins are first mixed, then mixed with ceramic particles, and then coated on the aluminum foil at the edge of the positive electrode to form a functional coating, and then hot pressed with the PP / PE / ceramic diaphragm. The soft segment resin can achieve bonding with the PP / PE / ceramic diaphragm, and the hard segment resin can achieve bonding with the aluminum foil. At the same time, during hot pressing, the resin will flow to the pores of the diaphragm and achieve a high-strength riveted structure through post-curing. Through the above design, bonding between the diaphragm and the aluminum foil can be achieved, the production process can be optimized, production efficiency can be improved, and production costs can be reduced; at the same time, the wettability of the electrolyte can be improved, and the high-rate cycle performance of the battery cell can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a diagram of a material stringing test in Example 1 of the present invention; Figure 2 This is a test diagram of material stringing in Comparative Example 1 of the present invention; In the figure: 1- positive electrode ear slurry, 2- positive electrode slurry. DETAILED DESCRIPTION

[0038] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the embodiments described herein are part of the embodiments of the present invention, rather than all of the embodiments, and are only used to explain the present invention, not to limit the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the protection scope of the present invention.

[0039] It should be noted that: In the present invention, the acrylic polymer is a general term for acrylic resins copolymerized from acrylic monomers containing ester bonds (such as methyl acrylate, isooctyl acrylate, etc.) or unsaturated olefin monomers (such as styrene, etc.).

[0040] In the present invention, the content of the relevant structural unit in the acrylic polymer is calculated as the weight percentage of the monomer of the relevant structural unit in the total monomer. For example, the content of the structural unit containing carboxyl in the acrylic polymer is the weight percentage of the monomer of the structural unit containing carboxyl in the preparation of the positive electrode ear glue in the total monomer used.

[0041] In the present invention, the structural unit in a polymer or resin refers to the corresponding structure existing in the polymer or resin after the raw material monomers used in preparing the polymer or resin participate in the polymerization.

[0042] In the first aspect, the positive electrode ear glue provided by the present invention includes an acrylic polymer, an organic salt and an organic solvent, the molecular weight Mw of the acrylic polymer is 10w~35w, and the weight percentage of the organic salt in the acrylic polymer is 0.1%~0.8%; the acrylic polymer includes a hard segment resin and a soft segment resin, the glass transition temperature Tg of the hard segment resin is ≥ 20°C, and the glass transition temperature Tg of the soft segment resin is ≤ 0°C.

[0043] In the positive electrode tab glue, if the weight percentage of organic salt in the acrylic polymer is greater than 0.8%, the positive electrode tab slurry and the positive electrode slurry will penetrate each other; if the weight percentage of organic salt in the acrylic polymer is less than 0.1%, the wettability of the slurry will decrease, resulting in coating omissions.

[0044] In the positive electrode tab glue, if the molecular weight Mw of the acrylic polymer is less than 10w, the viscosity of the slurry decreases, and the positive electrode tab slurry and the positive electrode slurry penetrate each other; if the molecular weight Mw of the acrylic polymer is greater than 35w, due to the large molecular weight, the chain segments are difficult to move during hot pressing, and the bonding strength with the diaphragm decreases.

[0045] Methods for controlling the molecular weight of acrylic polymers are well known to those skilled in the art, such as adjusting the initiator concentration, using a chain transfer agent, and controlling the reaction conditions (time, temperature, stirring speed, etc.). In the present invention, it is preferred to use a chain transfer agent to control the molecular weight of the acrylic polymer. In the present invention, various chain transfer agents commonly used in the prior art can be used, such as mercaptans and thiol compounds, specifically dodecanethiol. The amount of chain transfer agent added is adjusted according to the molecular weight of the acrylic polymer to be obtained, and the method for adjusting the amount of addition is well known to those skilled in the art.

[0046] Preferably, the content of the structural unit containing carboxyl groups in the acrylic polymer is 2-15%. If the content of the structural unit containing carboxyl groups in the acrylic polymer is less than 2wt%, the ceramic cannot be effectively dispersed; if the content of the structural unit containing carboxyl groups in the acrylic polymer is greater than 15wt%, the system is unstable.

[0047] Therefore, in order to meet the requirements of the present application for the safety of the positive electrode ear glue and strong dry adhesion strength and wet adhesion strength, the molecular weight Mw of the acrylic polymer of the present application is limited to 10w~35w, specifically 10w, 12w, 14w, 18w, 22w, 24w, 26w, 28w, 30w or 35w, etc.; the content of the structural unit containing a carboxyl group in the acrylic polymer is limited to 2~15wt%, specifically 2wt%, 3wt%, 5wt%, 8wt%, 10wt%, 12wt% or 15wt%, etc.; the weight percentage of the organic salt in the acrylic polymer is limited to 0.1%~0.8%, specifically 0.1%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7% or 0.8%, etc., preferably 0.4%~0.8%.

[0048] In some specific embodiments, the acrylic polymer includes a hard segment resin and a soft segment resin. The larger the Tg of the hard segment resin, the weaker the dry adhesion strength, and the less affected the wet adhesion strength; the lower the Tg of the soft segment resin, the higher the dry adhesion strength and the lower the wet adhesion strength. Therefore, in order to make the dry adhesion strength and wet adhesion strength of the positive electrode ear glue relatively high, the present application defines the glass transition temperature Tg of the hard segment resin ≥ 20°C, specifically 20°C, 30°C, 45°C, 67°C, 82°C or 90°C, etc., and the glass transition temperature Tg of the hard segment resin is preferably 20~90°C; the glass transition temperature Tg of the soft segment resin is ≤ 0°C, specifically 0°C, -10°C, -20°C, -30°C, -40°C, -50°C or -60°C, etc., and the glass transition temperature Tg of the soft segment resin is preferably -60 ~ 0°C.

[0049] When the soft segment accounts for a large proportion, the wet adhesion strength decreases and the dry adhesion strength increases. In order to make the dry adhesion strength and wet adhesion strength of the positive electrode ear glue relatively high, the mass ratio of the hard segment resin to the soft segment resin is (20~35): (65~80). Specifically, the mass ratio of the hard segment resin to the soft segment resin can be 20:80, 24:76, 28:72, 32:68 or 35:65, etc.

[0050] In some specific embodiments, the hard segment resin includes a first main structural unit and a first polar structural unit; the soft segment resin includes a second main structural unit and a second polar structural unit; the first main structural unit and the second main structural unit both include acrylate structural units, and each independently and selectively contains an aromatic vinyl structural unit, and the first polar structural unit and the second polar structural unit are independently selected from structural units containing polar groups; the polar groups include one or more of carboxyl, cyano, hydroxyl, epoxy, amino, amide, and acetoxy.

[0051] In some specific embodiments, the mass ratio of the first main structural unit to the first polar structural unit is (80-97):(3-20); the mass ratio of the second main structural unit to the second polar structural unit is (75-97):(3-25).

[0052] In some specific embodiments, the acrylic acid ester structural unit is selected from one or more of methyl methacrylate structural unit, methyl acrylate structural unit, ethyl acrylate structural unit, butyl acrylate structural unit, sine octyl acrylate structural unit, isooctyl acrylate structural unit, hexyl acrylate structural unit, cyclohexyl methacrylate structural unit, isobornyl acrylate structural unit, and isobornyl methacrylate structural unit. The aromatic vinyl structural unit is selected from one or a combination of styrene structural unit and methyl styrene structural unit.

[0053] In some specific embodiments, the first polar structural unit and the second polar structural unit can be independently selected from one or a combination of two of a methacrylic acid structural unit, an acrylic acid structural unit, an acrylonitrile structural unit, a hydroxyethyl acrylate structural unit, a hydroxyethyl methacrylate structural unit, a hydroxypropyl methacrylate structural unit, a glycidyl methacrylate structural unit, an allyl glycidyl ether structural unit, a dimethylaminoethyl acrylate structural unit, a dimethylaminoethyl methacrylate structural unit, a tert-butylaminoethyl methacrylate structural unit, an acrylamide structural unit, a diacetone acrylamide structural unit, a hydroxymethyl acrylamide structural unit, an acetoacetoxyethyl methacrylate structural unit, a butyl itaconate structural unit, and a β-acryloxypropionic acid structural unit.

[0054] In some specific embodiments, the carboxyl-containing structural unit in the acrylic ester polymer is selected from methacrylic acid structural unit and acrylic acid structural unit, or a combination of both.

[0055] The acrylic ester structural units, aromatic vinyl structural units, polar structural units, etc. selected from the hard segment resin and the soft segment resin may be the same or different and must meet the corresponding glass transition temperature Tg requirements.

[0056] In some specific embodiments, the hard segment resin further includes a first post-reaction structural unit containing a post-reaction group, and the soft segment resin further includes a second post-reaction structural unit containing a post-reaction group, and the first post-reaction structural unit and the second post-reaction structural unit are connected to each other through a chemical bond. It can be understood that the above structure can be obtained by reacting the first post-reaction monomer containing a post-reaction group with the second post-reaction monomer containing a post-reaction group. At this time, the hard segment resin and the soft segment resin are polymerized into one, which is very beneficial to improving the bonding force.

[0057] The higher the proportion of the post-reaction group, the greater the dry and wet peel strengths. When the peel strength exceeds a certain range, it decreases, and when the proportion is greater than 10%, the system is unstable. Based on this, the present application further defines that the first post-reaction structural unit accounts for 3-10% of the weight of the hard segment resin, specifically 3%, 5%, 6.3%, 8%, 9.1% or 10%, etc.; the structural unit of the second post-reaction group accounts for 3-10% of the weight of the soft segment resin, specifically 3%, 4%, 6%, 7.5%, 8.4% or 10%, etc.

[0058] In some specific embodiments, the post-reaction group is selected from one or more of carboxyl, amino, epoxy, and acetoxy groups; it is understandable that the post-reaction group on the first post-reaction monomer must be able to react with the post-reaction group on the second post-reaction monomer. For example, the post-reaction group in the first post-reaction monomer is a carboxyl group and / or an amino group, and the corresponding post-reaction groups in the second post-reaction monomer are epoxy and / or acetoxy groups. That is, when the post-reaction group in the first post-reaction monomer is a carboxyl group, the post-reaction group in the second post-reaction monomer is an epoxy group; when the post-reaction group in the first post-reaction monomer is an amino group, the post-reaction group in the second post-reaction monomer is an epoxy group and / or an acetoxy group. In this way, when the hard segment resin is mixed with the soft segment resin, it will be post-cured at ≥80°C.

[0059] In some specific embodiments, the first post-reaction monomer is selected from one or more of β-acryloxypropionic acid, methacrylic acid, acrylic acid, dimethylaminoethyl acrylate, dimethylaminoethyl methacrylate, tert-butylaminoethyl methacrylate, glycidyl methacrylate, allyl glycidyl ether, and acetoacetoxyethyl methacrylate; the second post-reaction monomer is selected from one or more of β-acryloxypropionic acid, methacrylic acid, acrylic acid, dimethylaminoethyl acrylate, dimethylaminoethyl methacrylate, tert-butylaminoethyl methacrylate, glycidyl methacrylate, allyl glycidyl ether, and acetoacetoxyethyl methacrylate.

[0060] Specifically, when the first post-reaction monomer in the hard segment resin is one or more of butyl itaconate, β-acryloxypropionic acid, methacrylic acid, acrylic acid, etc., the second post-reaction monomer in the soft segment resin is one or more of glycidyl methacrylate, allyl glycidyl ether, etc.

[0061] Specifically, when the first post-reaction monomer in the hard segment resin is one or more of dimethylaminoethyl acrylate, dimethylaminoethyl methacrylate, tert-butylaminoethyl methacrylate, etc., the second post-reaction monomer in the soft segment resin is one or more of glycidyl methacrylate, allyl glycidyl ether, acetoacetoxyethyl methacrylate, etc.

[0062] In the hard segment resin, the monomers forming the first polar structural unit include the first post-reaction monomer and the monomers of other polar structural units; the monomers forming the first polar structural unit may be the same as the first post-reaction monomer. When the monomers forming the first polar structural unit are the same as the first post-reaction monomer, the amount of the monomers of the first polar structural unit only needs to satisfy the range of the mass ratio of the first main structural unit to the first polar structural unit, and the structural unit of the first post-reaction group accounts for 3-10% of the weight of the hard segment resin.

[0063] Similarly, in the soft segment resin, the monomers forming the second polar structural unit include the second post-reaction monomer and the monomers of other polar structural units; the monomers forming the second polar structural unit can be the same as the second post-reaction monomer. When the monomers forming the second polar structural unit are the same as the second post-reaction monomer, the amount of the monomers of the second polar structural unit only needs to satisfy the range of the mass ratio of the second main structural unit to the second polar structural unit, and the structural unit of the second post-reaction group accounts for 3-10% of the weight of the soft segment resin.

[0064] Preferably, the molar ratio of the post-reaction group on the first post-reaction monomer to the post-reaction group on the second post-reaction monomer is (0.9-1.1): 1. In the present invention, when the molar ratio of the two is not within the above preferred range, the presence of the excess post-reaction group does not significantly affect the performance of the positive electrode ear glue.

[0065] When the monomer forming the first polar structural unit, the monomer forming the second polar structural unit and the first post-reaction monomer all contain carboxyl groups, the mass ratio of the total amount of carboxyl-containing monomers in the monomer forming the first polar structural unit and the monomer forming the second polar structural unit to the total amount of monomers for preparing the acrylic polymer is taken as the content of the structural unit containing carboxyl groups in the acrylic polymer.

[0066] In some specific embodiments, the solid content of the positive electrode ear glue is 18-22%, specifically 18%, 19%, 20%, 21% or 22%, etc. The organic salt includes at least one of alkyl sulfonate, alkyl sulfate, and alkylbenzene sulfonate, specifically dioctyl sodium sulfosuccinate, dihexyl sodium sulfosuccinate, sodium dodecyl sulfate, sodium hexadecyl sulfate, sodium octadecyl sulfate or sodium dodecylbenzene sulfonate, etc. Considering the simultaneous coating of the positive electrode ear glue slurry and the positive electrode slurry, the common solvent of the positive electrode slurry is NMP (N-methylpyrrolidone), so the organic solvent in the positive electrode ear glue is preferably NMP.

[0067] In some specific embodiments, the positive electrode ear glue is used for a ternary positive electrode. When it is coated simultaneously with the ternary positive electrode slurry, the molecular weight Mw of the acrylic polymer is 10w~35w, and specifically can be 10w, 13.6w, 15.2w, 17.8w, 20.3w, 25w, 27.7w, 30w, 32w or 35w, etc. Alternatively, the positive electrode ear glue is used for a lithium iron phosphate positive electrode. When it is coated simultaneously with the lithium iron phosphate slurry, the molecular weight Mw of the acrylic polymer is 20w~35w, and specifically can be 20w, 22w, 24w, 25.6w, 27.8w, 30w, 32w or 35w, etc. In this way, the positive electrode ear glue slurry is coated simultaneously with the positive electrode slurry without cross-linking.

[0068] In a second aspect, the present invention provides a positive electrode ear glue slurry, comprising ceramic particles and the aforementioned positive electrode ear glue, wherein the mass ratio of the ceramic particles to the positive electrode ear glue is (80~95):(5~20), specifically 80:20, 85:15, 88:12, 92:8 or 95:5, etc. The positive electrode ear glue binder and the ceramic particles are mixed in proportion to obtain the positive electrode ear glue slurry. Preferably, the mass ratio of the ceramic particles to the positive electrode ear glue is (80~85):(15~20).

[0069] In a third aspect, the present invention provides a positive electrode sheet, including a functional coating obtained by drying the positive electrode tab slurry. The positive electrode tab slurry and the positive electrode slurry are simultaneously coated on the aluminum foil at the edge of the positive electrode sheet, and dried to obtain a positive electrode sheet with a functional coating.

[0070] In a fourth aspect, the present invention provides a secondary battery comprising a negative electrode sheet, a separator, an electrolyte and the aforementioned positive electrode sheet.

[0071] Preparation method of positive electrode ear glue of the present application: First, a monomer that meets the requirements of the hard / soft segment resin is selected, and a chain transfer agent is added according to the molecular weight requirement. The chain transfer agent is preferably dodecanethiol, and the addition amount accounts for 0.02-0.05% of the total weight of the monomer; after adding 0.1-0.8% of the total weight of the monomer and mixing with an appropriate amount of organic salt and an organic solvent, an initiator is added, and the initiator is azobisisobutyronitrile or azobisisoheptanenitrile, and the initiator accounts for 1-2% of the total weight of the monomer. The reaction is carried out at a temperature of 70-90° C. for 12-20 hours to obtain a hard segment resin solution and a soft segment resin solution, respectively; the hard segment resin solution and the soft segment resin solution are mixed according to a mass ratio of the hard segment resin (total weight of the monomer) to the soft segment resin (total weight of the monomer) of (20-35): (65-80), and the reaction is carried out at 90-100° C., and then the amount of NMP solvent is adjusted so that the solid content is 18-22%, to obtain an acrylic polymer solution, that is, a positive electrode ear glue.

[0072] As mentioned above, the positive electrode tab glue provided by the present invention is applicable to various types of positive electrode slurries commonly used at present. Among them, the composition and type of the positive electrode slurry can adopt various types commonly used in the prior art.

[0073] For example, the positive electrode slurry includes the following components by weight: 90-98 parts of positive electrode active material, 0.5-3 parts of binder, 1-5 parts of conductive agent and 0-0.5 parts of secondary battery auxiliary agent optionally added.

[0074] N-methylpyrrolidone solvent is used to disperse ternary positive electrode active particles of lithium nickel cobalt manganese oxide NCM523, conductive carbon black Super P and binder polyvinylidene fluoride to form a ternary NCM positive electrode slurry, wherein the mass ratio of the positive electrode active particles, the conductive agent and the binder is 97.5:1.0:1.5.

[0075] Alternatively, 3 parts of binder PVDF are dissolved in 400 parts of N-methylpyrrolidone solvent to prepare a solution, and 94 parts of positive electrode active material lithium iron phosphate, 2.6 parts of conductive carbon black and 0.4 parts of dispersant are added in sequence, the speed is 120r / min, and stirring is carried out for 30 minutes to make the powder material fully and evenly mixed in the solvent to obtain lithium iron phosphate positive electrode slurry.

[0076] The specific implementation modes of the present invention will be further explained below through examples and comparative examples.

[0077] Unless otherwise specified, the reagents, materials and instruments used in the following description are all conventional reagents, conventional materials and conventional instruments, which can be commercially obtained, and the reagents involved can also be synthesized by conventional synthesis methods. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art.

[0078] Monomers that meet the requirements of the present application can be obtained commercially. The glass transition temperature can be selected when purchasing, or can be tested by oneself, for example, by using a differential scanning calorimeter (DSC). The molecular weight Mw of the acrylic polymer can be measured by gel permeation chromatography (GPC).

[0079] Example 1 (1) Preparation of positive electrode ear glue: The monomer composition of the hard segment resin is: 58 parts of styrene, 27 parts of isooctyl acrylate, 15 parts of methacrylic acid (86 g / mol, a monomer forming the first polar structural unit, of which 4.3 parts are used as the first post-reaction monomer), and 0.05 parts of dodecanethiol; The monomer composition of the soft segment resin is: 75 parts of isooctyl acrylate, 15 parts of styrene, 3 parts of acrylonitrile (monomer forming the second polar structural unit), 7 parts of glycidyl methacrylate (142 g / mol, the monomer forming the second polar structural unit is also the second post-reaction monomer), and 0.05 parts of dodecanethiol; In the monomer composition of the hard segment resin, 0.4 parts of sodium dodecyl sulfate was added, mixed with an appropriate amount of NMP solvent, and then 1 part of azobisisobutyronitrile was added. The mixture was reacted at 75°C for 12 hours to obtain a solution of the hard segment resin, whose glass transition temperature Tg was 45.5°C.

[0080] In the monomer composition of the soft segment resin, 0.4 parts of sodium dodecyl sulfate was added, mixed with an appropriate amount of NMP solvent, and then 1 part of azobisisobutyronitrile was added. The mixture was reacted at 75°C for 12 hours to obtain a solution of the soft segment resin, whose glass transition temperature Tg was -40.3°C.

[0081] The hard segment resin solution and the soft segment resin solution were mixed at a mass ratio of 30:70, and then reacted at 90°C, and then the amount of NMP solvent was adjusted to make the solid content 20%, to obtain an acrylic polymer solution, that is, a positive electrode ear glue. The molecular weight Mw of the acrylic polymer is 18w, and the content of the structural unit containing a carboxyl group is 3.21%.

[0082] (2) Positive electrode tab slurry: The ceramic particles are mixed with the prepared positive electrode tab glue in a mass ratio of 85:15 to obtain the positive electrode tab slurry.

[0083] (3) Positive electrode slurry: N-methylpyrrolidone solvent is used to disperse ternary positive electrode active particles of lithium nickel cobalt manganese oxide NCM523, conductive carbon black Super P and binder polyvinylidene fluoride to form a ternary NCM positive electrode slurry, in which the mass ratio of positive electrode active particles, conductive agent and binder is 97.5:1.0:1.5.

[0084] Take one drop of the above-mentioned positive electrode ear glue slurry and positive electrode slurry, drop them into the container, and make the two slurries contact. If the boundary between the two drops of slurry is clear and there is no interpenetration, it is determined that there is no cross-linking; if the boundary is blurred and there is interpenetration, it is determined that cross-linking has occurred.

[0085] like Figure 1 As shown, the boundary between the positive electrode tab slurry 1 and the positive electrode slurry 2 is clear, and no cross-linking occurs.

[0086] (4) Positive electrode sheet: The positive electrode tab slurry and the ternary positive electrode slurry are simultaneously coated on aluminum foil to prepare a positive electrode sheet. The positive electrode tab slurry is coated on the aluminum foil at the edge of the positive electrode sheet. After drying, a positive electrode sheet with a functional coating is obtained.

[0087] (5) Preparation of lithium-ion secondary batteries: The negative electrode sheet, separator and electrolyte of the lithium ion battery prepared according to the conventional method in the art and the positive electrode sheet prepared by the present application are assembled into a lithium ion secondary battery according to the general process of preparing lithium ion batteries.

[0088] Example 2 According to the method of Example 1, positive electrode ear glue, positive electrode ear glue slurry, positive electrode sheet and lithium ion secondary battery are prepared. The main difference between Example 2 and Example 1 is that: Preparation of positive electrode ear glue: 0.1 parts of sodium hexadecyl sulfate and 0.045 parts of dodecanethiol were added to the monomer composition of hard / soft segment resin respectively; The positive electrode ear glue was prepared, and the molecular weight Mw of the acrylic ester polymer was 20w.

[0089] Example 3 According to the method of Example 1, positive electrode ear glue, positive electrode ear glue slurry, positive electrode sheet and lithium ion secondary battery are prepared. The main difference between Example 3 and Example 1 is that: Preparation of positive electrode ear glue: 0.8 parts of sodium dodecylbenzene sulfonate and 0.045 parts of dodecyl mercaptan are added to the monomer composition of hard / soft segment resin respectively; The positive electrode ear glue was prepared, and the molecular weight Mw of the acrylic ester polymer was 20w.

[0090] Example 4 According to the method of Example 1, positive electrode ear glue, positive electrode ear glue slurry, positive electrode sheet and lithium ion secondary battery are prepared. The main difference between Example 4 and Example 1 is that: Preparation of positive electrode ear glue: 0.025 parts of dodecanethiol were added to the monomer composition of hard / soft segment resin, and the mass ratio of hard segment resin to soft segment resin was 20:80; The positive electrode ear glue was prepared, and the molecular weight Mw of the acrylic ester polymer was 35w, wherein the content of the structural unit containing the carboxyl group was 2.14%.

[0091] Example 5 According to the method of Example 1, positive electrode tab glue, positive electrode tab glue slurry, positive electrode plate and lithium ion secondary battery are prepared. The main difference between Example 5 and Example 1 is that: Preparation of positive electrode ear glue: 0.025 parts of dodecanethiol were added to the monomer composition of hard / soft segment resin, and the mass ratio of hard segment resin to soft segment resin was 35:65; The positive electrode ear glue was prepared, and the molecular weight Mw of the acrylic ester polymer was 35w, wherein the content of the structural unit containing the carboxyl group was 3.75%.

[0092] Example 6 According to the method of Example 1, positive electrode tab glue, positive electrode tab glue slurry, positive electrode plate and lithium ion secondary battery are prepared. The main difference between Example 6 and Example 1 is that: Preparation of positive electrode tab slurry: The mass ratio of ceramic particles to positive electrode tab slurry is 80:20.

[0093] Example 7 According to the method of Example 1, positive electrode tab glue, positive electrode tab glue slurry, positive electrode plate and lithium ion secondary battery are prepared. The main difference between Example 7 and Example 1 is that: Preparation of positive electrode tab slurry: The mass ratio of ceramic particles to positive electrode tab slurry is 95:5.

[0094] Example 8 According to the method of Example 1, positive electrode ear glue, positive electrode ear glue slurry, positive electrode sheet and lithium ion secondary battery are prepared. The difference between Example 8 and Example 1 is that: The monomer composition of the hard segment resin is: 51 parts of methyl styrene, 29 parts of methyl acrylate, 15 parts of acrylic acid (monomer forming the first polar structural unit), 5 parts of dimethylaminoethyl acrylate (143 g / mol, monomer forming the first polar structural unit, of which 3.5 parts are used as the first post-reaction monomer), and 0.05 parts of n-dodecyl mercaptan; The monomer composition of the soft segment resin is: 45 parts of styrene, 50 parts of n-butyl acrylate, 5 parts of acetoacetoxyethyl methacrylate (214 g / mol, the monomer forming the second polar structural unit is also the second post-reaction monomer), and 0.05 parts of n-dodecyl mercaptan; The glass transition temperature Tg of the hard segment resin is 88.7°C. The glass transition temperature Tg of the soft segment resin is -0.1°C.

[0095] Example 9 According to the method of Example 1, positive electrode ear glue, positive electrode ear glue slurry, positive electrode sheet and lithium ion secondary battery are prepared. The difference between Example 9 and Example 1 is that: The monomer composition of the hard segment resin is: 41 parts of styrene, 39 parts of n-butyl acrylate, 15 parts of acrylic acid (72 g / mol, the monomer forming the first polar structural unit, of which 1 part is used as the first post-reaction monomer), 5 parts of tert-butylaminoethyl methacrylate (185.3 g / mol, the monomer forming the first polar structural unit is also the first post-reaction monomer), and 0.05 parts of n-dodecyl mercaptan; The monomer composition of the soft segment resin is: 2 parts of styrene, 93 parts of isooctyl acrylate, 5 parts of allyl glycidyl ether (114 g / mol, the monomer forming the second polar structural unit is also the second post-reaction monomer), and 0.05 parts of n-dodecyl mercaptan; The glass transition temperature Tg of the hard segment resin is 19.5°C. The glass transition temperature Tg of the soft segment resin is -59.3°C; The solution of the hard segment resin and the solution of the soft segment resin were mixed in a mass ratio of 30:70 between the hard segment resin (total mass of monomers) and the soft segment resin (total mass of monomers), and the mixture was reacted at 90°C. Then, the amount of NMP solvent was adjusted so that the solid content was 22%, to obtain an acrylic polymer solution, i.e., a positive electrode ear glue. The molecular weight Mw of the acrylic polymer was 20w.

[0096] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that a positive electrode ear glue of the PVDF system is selected.

[0097] The positive electrode ear glue and the positive electrode slurry of this comparative example were tested in the same manner as in Example 1 to see whether there was any cross-contamination. Figure 2 As shown, the boundary between the positive electrode tab slurry 1 and the positive electrode slurry 2 is blurred, and interpenetration occurs, resulting in cross-linking.

[0098] Comparative Example 2 According to the method of Example 1, positive electrode tab glue, positive electrode tab glue slurry, positive electrode plate and lithium ion secondary battery are prepared. The difference between Comparative Example 2 and Example 1 is that there is no organic salt in the positive electrode tab glue.

[0099] Comparative Example 3 According to the method of Example 1, positive electrode tab glue, positive electrode tab glue slurry, positive electrode plate and lithium ion secondary battery are prepared. The difference between Comparative Example 3 and Example 1 is that the weight percentage of organic salt in the acrylic ester polymer is 1%.

[0100] Comparative Example 4 Positive electrode ear glue, positive electrode ear glue slurry, positive electrode plate and lithium ion secondary battery were prepared according to the method of Example 1. The difference between Comparative Example 4 and Example 1 is that in the preparation of the positive electrode ear glue, 0.1 parts of dodecanethiol were added to the monomer composition of the hard / soft segment resin respectively, and the molecular weight Mw of the acrylic ester polymer was 5w.

[0101] Comparative Example 5 According to the method of Example 1, positive electrode ear glue, positive electrode ear glue slurry, positive electrode plate and lithium ion secondary battery are prepared. The difference between Example 5 and Example 1 is that in the preparation of the positive electrode ear glue, 0.01 parts of dodecanethiol are added to the monomer composition of the hard / soft segment resin respectively, and the molecular weight Mw of the acrylic ester polymer is 40w.

[0102] Comparative Example 6 According to the method of Example 1, positive electrode tab glue, positive electrode tab glue slurry, positive electrode plate and lithium ion secondary battery are prepared. The difference between Comparative Example 6 and Example 1 is that the mass ratio of the hard segment resin to the soft segment resin in the acrylic polymer is 60:40.

[0103] Comparative Example 7 According to the method of Example 1, positive electrode ear glue, positive electrode ear glue slurry, positive electrode sheet and lithium ion secondary battery are prepared. The difference between Comparative Example 7 and Example 1 is that: The monomer composition of the hard segment resin is: 68 parts of methyl styrene, 12 parts of isooctyl acrylate, 15 parts of acrylic acid (a monomer forming the first polar structural unit), 5 parts of dimethylaminoethyl acrylate (a monomer forming the first polar structural unit and also the first post-reaction monomer), and 0.05 parts of dodecanethiol; The monomer composition of the soft segment resin is 35 parts of styrene, 60 parts of ethyl acrylate, 5 parts of acetoacetoxyethyl methacrylate (the monomer forming the second polar structural unit is also the second post-reaction monomer), and 0.05 parts of dodecanethiol; The Tg of the hard segment resin in the acrylic polymer is 99.0℃, and the Tg of the soft segment resin is 12.7℃.

[0104] Comparative Example 8 According to the method of Example 1, positive electrode ear glue, positive electrode ear glue slurry, positive electrode sheet and lithium ion secondary battery are prepared. The difference between Comparative Example 8 and Example 1 is that: The monomer composition of the hard segment resin is: 31 parts of methyl styrene, 49 parts of n-butyl acrylate, 15 parts of acrylic acid (a monomer forming the first polar structural unit), 5 parts of dimethylaminoethyl acrylate (a monomer forming the first polar structural unit and also the first post-reaction monomer), and 0.05 parts of dodecanethiol; The monomer composition of the soft segment resin is 2 parts of styrene, 93 parts of allyl polyethylene glycol, 5 parts of acetoacetoxyethyl methacrylate (the monomer forming the second polar structural unit is also the second post-reaction monomer), and 0.05 parts of dodecanethiol; The Tg of the hard segment resin in the acrylic polymer is 9.3°C, and the Tg of the soft segment resin is -65.9°C.

[0105] Performance Test: The positive electrode tab slurry, positive electrode sheet and secondary battery prepared in the above embodiments and comparative examples were subjected to performance tests.

[0106] [Material cross-contamination] Take one drop of the positive electrode ear slurry and the positive electrode slurry prepared in this application, drop them into a container, and make the two slurries contact each other. If the boundary between the two drops of slurry is clear and there is no interpenetration, it is determined that there is no material cross-contamination; if the boundary is blurred and there is interpenetration, it is determined that material cross-contamination has occurred.

[0107] [Dry adhesion peel strength with foil] The positive electrode sheet prepared by the present application was cut into strips of 20*100 mm, pressed for 60 s at 100°C and 8 Mwa, and the coating peeling strength was tested using an electronic tensile testing machine (Dongguan Dazhong Instrument Co., Ltd., model DZ-101).

[0108] [Wet adhesion peel strength with foil] The positive electrode sheet prepared by this application was cut into 20*100mm strips, pressed for 60s at 100℃ and 8Mwa, immersed in 60℃ electrolyte for 3 days, taken out and dried, and then the coating peel strength was tested using an electronic tensile testing machine (Dongguan Dazhong Instrument Co., Ltd., Model DZ-101).

[0109] [Dry-peel strength with diaphragm] The positive electrode sheet and diaphragm prepared by the present application were cut into 20*100 mm strips respectively, pressed for 60 s at 100°C and 8 Mwa, and the bonding strength was tested using an electronic tensile testing machine (Dongguan Dazhong Instrument Co., Ltd., Model DZ-101).

[0110] [Wet adhesion peel strength with diaphragm] The positive electrode sheet and diaphragm prepared by the scheme of the present invention were cut into 20*100mm strips respectively, pressed for 60s at 100℃ and 8Mwa, immersed in 60℃ electrolyte for 3 days, taken out and dried, and then the bonding strength was tested using an electronic tensile testing machine (Dongguan Dazhong Instrument Co., Ltd., Model DZ-101).

[0111]

Battery cell internal resistance

[0112] [High-temperature storage capacity retention rate] The soft-pack batteries prepared in the above embodiments and comparative examples were discharged at a constant current of 0.5C to a voltage of 2.7V, and then charged at a constant current of 1C to a voltage of 4.3V, and then charged at a constant voltage to a cut-off current of 0.05C. After charging, they were discharged at a constant current of 1C to 2.75V, and the discharge capacity before storage was recorded as C0; they were then charged at a constant current of 1C to a voltage of 4.3V, and then charged at a constant voltage to a cut-off current of 0.05C, at which time the battery was fully charged; the aforementioned fully charged battery was discharged after being stored at 60°C for 30 days, and the discharge capacity after storage was recorded as C1, then the high-temperature storage capacity retention rate (%) = C1 / C0×100%.

[0113]

High rate cycle capacity retention rate

[0114] The performance test results are shown in Table 1.

[0115] Table 1:

[0116] It can be seen from the test results of Examples 1 to 9 and Comparative Example 1 that the present application adopts an acrylic polymer system instead of the traditional PVDF system as the positive electrode ear glue, which can improve the adhesion between the aluminum foil and the separator, especially the wet adhesion peel strength, thereby improving the processing performance and safety of the battery and improving the cycle performance of the battery cell.

[0117] From the test results of Examples 1 to 3 and Comparative Examples 2 to 3, it can be seen that in the positive electrode ear glue, the weight percentage of organic salt in the acrylic polymer is greater than 0.8%, and the positive electrode ear slurry and the positive electrode slurry have mutual penetration (cross-linking), which affects the gram capacity of the main material, and the capacity during high-temperature storage and high-rate cycling is reduced. No organic salt is added to the positive electrode ear glue, the wettability of the slurry decreases, there will be coating leaks, and the test battery cell has a short circuit. Analysis shows that the burrs during die cutting pierced the diaphragm. When the weight percentage of organic salt in the acrylic polymer is 0.4% to 0.8%, the performance is better.

[0118] It can be seen from the test results of Examples 1 to 5 and Comparative Examples 4 to 5 that when the molecular weight Mw of the acrylic polymer is less than 10w, the positive electrode tab slurry and the positive electrode slurry permeate each other (cross-linking), thereby affecting the gram capacity of the main material, and the capacity during high-temperature storage and high-rate cycling is reduced; when the molecular weight Mw of the acrylic polymer is greater than 35w, due to the large molecular weight, the chain segments are difficult to move during hot pressing, resulting in a decrease in the wet adhesion peel strength with the diaphragm, and the capacity during high-temperature storage and high-rate cycling is also reduced.

[0119] From the test results of Example 1, Examples 4-5 and Comparative Example 6, it can be seen that when the soft segment resin accounts for a large proportion, the wet peel strength with the foil and the diaphragm is significantly reduced, the dry peel strength with the diaphragm is increased, and the capacity during high-temperature storage and high-rate cycling is also reduced. When the mass ratio of the hard segment resin to the soft segment resin is (20-35): (65-80), the performance is better.

[0120] From the test results of Example 1, Example 8-9 and Comparative Examples 7-8, it can be seen that the lower the Tg of the soft segment resin, the higher the dry adhesive peel strength and the lower the wet adhesive peel strength; the higher the Tg of the hard segment resin, the smaller the dry adhesive strength and the smaller the wet adhesive peel strength; the capacity also decreases during high-temperature storage and high-rate cycling. When the Tg of the hard segment resin is 20-90°C and the glass transition temperature Tg of the soft segment resin is -60-0°C, the performance is better.

[0121] It can be seen from the test results of Examples 1 and 6-7 that when the mass ratio of ceramic particles to positive electrode ear glue in the positive electrode ear glue slurry is (80-85): (15-20), the performance in all aspects is better. It can be seen from the test results of Examples 1 and 8-9 that within the Tg range of the hard segment resin and the Tg range of the soft segment resin disclosed in the present invention, the lower the Tg of the soft segment resin, the lower the Tg of the hard segment resin, and the better the performance in all aspects.

[0122] It can be seen that the positive electrode ear glue of the acrylic polymer solution provided by the present invention can improve the wet adhesion strength. At the same time, the acrylic polymer solution has good flexibility and can effectively improve the curling of the aluminum foil. At the same time, due to its high wet adhesion strength, it can improve the processing performance and safety of the battery and improve the cycle performance of the battery cell.

[0123] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.

Claims

1. A positive electrode ear glue, characterized in that: The positive electrode ear glue comprises an acrylate polymer, an organic salt and an organic solvent, the molecular weight Mw of the acrylate polymer is 10w-35w, and the weight percentage of the organic salt to the acrylate polymer is 0.1%-0.8%; The acrylic polymer comprises a hard segment resin and a soft segment resin, the hard segment resin has a glass transition temperature Tg≥20°C, and the soft segment resin has a glass transition temperature Tg≤0°C.

2. The positive electrode ear glue according to claim 1, characterized in that: The glass transition temperature Tg of the hard segment resin is 20 to 90°C, and the glass transition temperature Tg of the soft segment resin is -60 to 0°C.

3. The positive electrode ear glue according to claim 1, characterized in that: The hard segment resin includes a first main structural unit and a first polar structural unit; the soft segment resin includes a second main structural unit and a second polar structural unit; the first main structural unit and the second main structural unit both include acrylate structural units, and each independently and selectively contains an aromatic vinyl structural unit, the first polar structural unit and the second polar structural unit are independently selected from structural units containing polar groups; the polar groups include one or more of carboxyl, cyano, hydroxyl, epoxy, amino, amide, and acetoxy.

4. The positive electrode ear glue according to claim 3, characterized in that: The mass ratio of the first main structural unit to the first polar structural unit is (80-97): (3-20); the mass ratio of the second main structural unit to the second polar structural unit is (75-97): (3-25).

5. The positive electrode ear glue according to claim 3 or 4, characterized in that: The content of the structural unit containing carboxyl groups in the acrylic ester polymer is 2-15 wt %.

6. The positive electrode ear glue according to claim 1, characterized in that: The mass ratio of the hard segment resin to the soft segment resin is (20-35):(65-80).

7. The positive electrode ear glue according to claim 1, characterized in that: The solid content of the positive electrode ear glue is 18-22%, the organic salt includes at least one of alkyl sulfonate, alkyl sulfate, and alkylbenzene sulfonate, and the organic solvent includes NMP.

8. A positive electrode tab slurry, characterized in that: It comprises ceramic particles and the positive electrode ear glue according to any one of claims 1 to 7, wherein the mass ratio of the ceramic particles to the positive electrode ear glue is (80 to 95): (5 to 20).

9. A positive electrode sheet, characterized in that: It comprises a functional coating obtained by drying the positive electrode tab slurry as described in claim 8.

10. A secondary battery, characterized in that: It comprises a negative electrode sheet, a separator, an electrolyte and the positive electrode sheet as claimed in claim 9.

Citation Information

Patent Citations

  • Composition for adhesive layer of non-aqueous secondary battery, adhesive layer of non-aqueous secondary battery, separator equipped with adhesive layer of non-aqueous secondary battery, electrode equipped with adhesive layer of non-aqueous secondary battery, non-aqueous secondary battery, and method for producing same

    CN108140785A

  • Binder for electrochemical devices, electrode mixture, electrode, electrochemical device and secondary battery

    CN113169303A

  • Positive electrode edge coating protection hot-pressing adhesive as well as preparation and application thereof

    CN117625091A

  • Novel binder for lithium ion battery aluminum foil edge coating and application

    CN119039910A

  • Dispersant for improved battery electrode formulations

    US20150083976A1

Cited By

  • Diaphragm binder composition, diaphragm and lithium ion secondary battery

    CN120775524A